2020
DOI: 10.35808/ersj/1817
|View full text |Cite
|
Sign up to set email alerts
|

National Strategic Documents on Cluster Policy as a Source of Challenges for Cluster Management in Poland

Abstract: Purpose: This paper is aimed to assess the evolution of Polish cluster policy, as well as, to identify the key challenges for cluster management in Poland, which result from the framework of the conditions described by the national strategic documents in the field of cluster policy. Literature review reveals a substantial shortage of publications and research in the area of the issue under discussion, and presents the relevant research gap. Design/Methodology/Approach: So far, no document strictly dedicated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Poruszają kwestie prac badawczych w zakresie nowoczesnych, innowacyjnych materiałów i powłok do produkcji samolotów oraz ich komponentów, jak również zagadnienia odnoszące się do silników turboodrzutowych i turbośmigłowych (opisujące parametry pracy silników, wpływ warunków otoczenia na osiągi samolotu), wytwarzania detali z zastosowaniem metod przyrostowych lub hybrydowych, prototypu pierwszego w Polsce statku powietrznego wykorzystującego ogniwa wodorowe do zasilania napędu elektrycznego -motoszybowca AOS -H2, zastosowania ogniwa paliwowego, nowych układów napędowych, takich jak napęd rozproszony (Orkisz, Wygonik, Kuźniar, Kalwara, 2019;Kalwara, Kuźniar, Orkisz, 2021), bardziej ekologicznych rozwiązań optymalizacyjnych w lotnictwie (Pawlak, Majka, Kuźniar, Pawluczy, 2018a, 2018b, 2020, zarządzania ruchem lotniczym, w tym planowania tras ruchu lotniczego (Samolej et al, 2021;Pawlak et al, 2018;Pawlak, Kuźniar, Majka, 2022), klastrów, m.in. lotniczych i kosmicznego (Stankiewicz, Mróz, Hajduk -Stelmachowicz, 2009;Bembenek, Frankowska, Myszak, 2020), technik kosmicznych, zarządzania bezpieczeństwem w lotnictwie (Michalski, Jurgilewicz, Kubiak, Grądzka, 2020) -także wobec wyzwań związanych z pandemią COVID-19 (Zboch, Hajduk -Stelmachowicz, Grzybowski, 2022), bezzałogowych statków powietrznych tzw. dronów, dróg / scenariuszy rozwojowych lotnictwa (Orkisz, Kuźniar, 2020).…”
Section: Wstępunclassified
“…Poruszają kwestie prac badawczych w zakresie nowoczesnych, innowacyjnych materiałów i powłok do produkcji samolotów oraz ich komponentów, jak również zagadnienia odnoszące się do silników turboodrzutowych i turbośmigłowych (opisujące parametry pracy silników, wpływ warunków otoczenia na osiągi samolotu), wytwarzania detali z zastosowaniem metod przyrostowych lub hybrydowych, prototypu pierwszego w Polsce statku powietrznego wykorzystującego ogniwa wodorowe do zasilania napędu elektrycznego -motoszybowca AOS -H2, zastosowania ogniwa paliwowego, nowych układów napędowych, takich jak napęd rozproszony (Orkisz, Wygonik, Kuźniar, Kalwara, 2019;Kalwara, Kuźniar, Orkisz, 2021), bardziej ekologicznych rozwiązań optymalizacyjnych w lotnictwie (Pawlak, Majka, Kuźniar, Pawluczy, 2018a, 2018b, 2020, zarządzania ruchem lotniczym, w tym planowania tras ruchu lotniczego (Samolej et al, 2021;Pawlak et al, 2018;Pawlak, Kuźniar, Majka, 2022), klastrów, m.in. lotniczych i kosmicznego (Stankiewicz, Mróz, Hajduk -Stelmachowicz, 2009;Bembenek, Frankowska, Myszak, 2020), technik kosmicznych, zarządzania bezpieczeństwem w lotnictwie (Michalski, Jurgilewicz, Kubiak, Grądzka, 2020) -także wobec wyzwań związanych z pandemią COVID-19 (Zboch, Hajduk -Stelmachowicz, Grzybowski, 2022), bezzałogowych statków powietrznych tzw. dronów, dróg / scenariuszy rozwojowych lotnictwa (Orkisz, Kuźniar, 2020).…”
Section: Wstępunclassified
“…These clusters have a high scientific and technological potential. These clusters are selected at the country level based on criteria concerning e.g., critical mass, innovation or development potential, planned and existing cooperation, as well as the experience and potential of the cluster coordinator (Frankowska et al, 2020). The second group is the Key Regional Clusters (KRC), which constitute the greatest competitive potential for the region's economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study confirmed some observations by other authors; for example, Citkowski notices that a small scale of cluster policy and a universal set of instruments (instead of "made to measure") diminishes the competitiveness of enterprises and whole regions [85], and therefore can be classified as a failure. Frankowska et al considered an inconsistency in cluster policy planning as one of the weaknesses [86]. This lack of long-term policy prevented long-term planning at the cluster level, which resulted in lower than expected effects of cluster policy.…”
mentioning
confidence: 99%